Behavioral economics—A framework for donor organ decision‐making in pediatric heart transplantation. (27th January 2020) - Butler, Alison; Chapman, Gretchen; Johnson, Jonathan N.; Amodeo, Antonio; Böhmer, Jens; Camino, Manuela; Davies, Ryan R.; Dipchand, Anne I.; Godown, Justin; Miera, Oliver; Pérez‐Blanco, Alicia; Rosenthal, David N.; et al.
Abstract: The high discard rate of pediatric donor hearts presents a major challenge for children awaiting heart transplantation. Recent literature identifies several factors that contribute to the disparities in pediatric donor heart usage, including regulatory oversight, the absence of guidelines on pediatric donor heart acceptance, and variation among transplant programs. However, a likely additional contributor to this issue are the behavioral factors influencing transplant team decisions in donor offer scenarios, a topic that has not yet been studied in detail. Behavioral economics and decision psychology provide an excellent foundation for investigating decision‐making in the pediatric transplant setting, offering key insights into the behavior of transplant professionals. We conducted a systematic review of published literature in pediatric heart transplant related to behavioral economics and the psychology of decision‐making. In this review, we draw on paradigms from these two domains in order to examine how existing aspects of the transplant environment, including regulatory oversight, programmatic variation, and allocation systems, may precipitate potential biases surrounding donor offer decisions. Recognizing how human decision behavior influences donor acceptance is a first step toward improving utilization of potentially viable pediatric donor hearts.